Buckling of vertical oil storage steel tanks: Review of static buckling studies. (June 2016) - Godoy, Luis A.
Abstract: Research on the structural behavior and buckling of vertical, aboveground tanks employed to store oil and fuels have significantly increased during the past two decades. Interest in this shell form is related not just to the cost of the infrastructure, but also because failures in cases of accidents or natural disasters may cause huge economic, environmental and social losses. This review concentrates on buckling problems of such tanks under static or quasi-static loads, including uniform pressure, wind, settlement of foundation, and fire. In all cases, buckling is considered as a static process. Attention is given to the load definition in each case, followed by buckling studies under previously defined pressures or temperatures. The structural configuration of tanks is first described in order to understand what is specific about this structural form. Next, the theoretical framework for stability and buckling is briefly described to place each contribution in a wider context. Each loading case is first explained, experiments or case-studies are briefly described, and computational analytical modeling is reviewed; finally, efforts towards improving design are mentioned. Most papers published in the literature have been motivated by wind effects on tanks, but the review shows that other areas, such as thermal buckling under an adjacent fire, are currently receiving increasing attention. Highlights: Brings together significant contributions to the buckling analysis and design of oil-storage tanks. Highlights the effects of uniform pressure, wind loads, settlement of the foundation, and fire as sources of buckling of tanks. Reviews the main trends in the definition of pressures and temperatures acting on tanks based on experiments and simulations. Provides possible directions for future research in this field for each loading considered.